Genetics of alternative definitions of feed efficiency in grazing lactating dairy cows - Hurley, AM; Lopez-Villalobos, N; McParland, S; Lewis, E; Kennedy, E; O'Donovan, M; Burke, JL; Berry, DP (NZSAP)
The objective of this study was to estimate genetic parameters for measures of energy conversion efficiency (ECE), energy balance (EB), net energy intake (NEI), net energy of lactation (NEL) and body weight (BW), within lactation stages in grazing dairy cows. Individual measurements of NEI (n=7,675) from 2,445 lactations on 1,245 grazing cows were available. Residual energy intake (REI) was defined as NEI minus predicted energy requirements; residual energy production (REP) was defined as net energy of lactation (NEL) minus predicted energy requirements. Energy conversion efficiency was defined as NEL divided by NEI; EB was defined as the difference between intake and energy required for maintenance plus lactation. Lactation was divided into three stages (8-90, 91-180, and >180 days in milk [DIM]). Genetic and phenotypic (co)variances for EB, NEL and BW were estimated using univariate and bivariate animal repeatability models. The models included the fixed effects of contemporary group (treatment and test-date), parity, DIM, as well as a random additive genetic effect of animal, a within-lactation stage random permanent environmental effect and an across-lactation permanent environmental effect. Heritability across-lactation stages varied from 0.13 (8-90 DIM) to 0.28 (91-180 DIM) for NEI, from 0.16 (8-90 DIM) to 0.33 (91-180 DIM) for NEL, from 0.04 (8-90 DIM) to 0.10 (91-180 and >180 DIM) for EB, from 0.03 (8-90 DIM) to 0.11 (>180 DIM) for REI, and from 0.04 (8-90 DIM) to 0.18 (>180 DIM) for ECE. A strong genetic association between REI and EB was evident when average BW change was close to zero. These genetic parameters from Holstein-Friesian dairy cows fed predominantly grazed grass imply that genetic improvement in selected efficiency traits is achievable.
Keywords: genetics; hertiability; feed efficiency; residual energy intake; 0702 Animal Production